Accounting for Sources of Information in Trade Fairs: Evidence from Portuguese Exhibitors - Silva, Pedro M. da (2021)
Trade fairs are important sources of information for decision making in marketing management. Currently, trade fairs are places where participants share useful data and information, while creating relationships between customers (visitors) and suppliers (exhibitors). However, only a limited number of studies have focused on the identification of the sources of information that exhibitors can provide for marketing managers at trade fairs. This study examines the importance of the different types of information resources that can be delivered by exhibitors to managers in order to transfer information about product and market trends. Based on the data from a survey of 172 Portuguese executives from different industries, the theoretical hypotheses are tested, using CFA (Confirmatory Factor Analysis). Consistent with our hypotheses, the results show that Direct Marketing techniques, such as face-to-face contacts and product/service demonstrations, are often used by exhibitors. Information in digital formats and demonstration in digital equipment (Digital Marketing) are also used in trade fairs to display information to potential customers. Additionally, the organization of parallel events (Event Marketing) during a trade fair supplements the package of activities developed by exhibitors to transmit and capture information for their companies. These results provide certain support for the importance of trade fairs in view of being a rich source of market information about not only new technological developments of products, but also major strengths and weaknesses of competitors, and future market trends, among other types of information needed for the marketing planning.